Development of Mathematical Model for Pyruvate Decarboxylase Deactivation Kinetics by Benzaldehyde with Inorganic Phosphate Activation Effect - Julaluk Khemacheewakul (Science Faculty of Chiang Mai University, 2019)
The effect of phosphate concentrations at 20, 250, 500, and 1,000 mM on phenylacetylcarbinol (PAC) production, pyruvate decarboxylase (PDC) deactivation kinetics, and combination of phosphate activation effect in a mathematical model were evaluated in a biotransformation system using whole cells of Candida tropicalis TISTR 5350. This is the first report of phosphate activation effect on pyruvate decarboxylase deactivation model. The highest PAC concentration (28.6 ± 2.3 mM), average instantaneous PAC formation rate (0.57 ± 0.01 mM/min), PAC yields (0.95 ± 0.08 on benzaldehyde and 0.71 ± 0.06 on pyruvate) were achieved in 1,000 mM phosphate buffer. PDC volumetric activity of 0.52 ± 0.07 U carboligase/ml at the reaction time of 180 min was obtained. The mathematical model describing deactivation kinetics of whole cells PDC by benzaldehyde with activation effect for phosphate buffer concentration level predicted individual experimental data for all four levels of phosphate buffer relatively well with corresponding residual sum of square (RSS), mean square (MS), and correlation coefficient (R2) range of 213-1,100, 5.32-27.5, and 0.96-0.99. The activation effect of 1,000 mM phosphate buffer was evident with an average enzyme activation rate constant due to buffering species concentration level (Ka) of 1.34 ´ 10-2 % min-1 which was higher than 20 mM phosphate buffer (1.48 ´ 10-6 % min-1) by more than 9,050 times.